Co-designing a motivational interviewing training platform to enhance oncology healthcare professional communication - Thu Ha Dang; Chris Ludlow; Hannah Borle; Marliese Alexander; Nilmini Wickramasinghe; Kate Burbury; Prem Prakash Jayaraman; Penelope Schofield (PEC Innovation)
Background: Oncology healthcare professionals (HCPs) using motivational interviewing may motivate and support patients with chronic illness to adhere to medications. Research of online motivational interviewing training focusing on medication adherence in cancer is limited. Objective: Co-design, develop, and preliminarily evaluate a motivational interviewing training platform (MITP) for oncology HCPs focused on medication adherence. Methods: We used co-design and design science research methodology to develop and test the MITP in two phases: 1) program co-design and development and 2) interactive platform design and development. Results: HCPs expressed a high demand for a practical and tailored motivational interviewing training. MITP is an online three-hour training comprising education, roleplay videos, and formative assessments. MITP was reported to be acceptable, usable, and useful by users. Innovation: This study used a novel approach combining co-design and design science research methodology, and digital media to develop a flexible and acceptable online motivational interviewing training focused on medication adherence in cancer. Discussion and conclusion: Applied rigorous methodology ensured the MITP was developed to address knowledge gaps and the needs of oncology HCPs for supporting patient adherence, and to be usable and useful. Study findings may inform future research on online motivational interviewing training and its potential impact on medication adherence.